"Negotiating a new normality" - a longitudinal qualitative exploration of the meaning of living with an open surgical wound. Issue 1 (31st December 2022) - Pađen, Ljubiša; Griffiths, Jane; Cullum, Nicky
ABSTRACT: Purpose: Little is known about the experiences of people living with open surgical wounds. These wounds are common and predominantly affect young and actively working people. The aim of this qualitative study was to explore the meaning of living with open surgical wounds. Methods: A qualitative exploratory study was conducted. We collected data using two individual interviews with each of ten participants (aged between 18–73 years) who had open surgical wounds. Our analytical approach was based on qualitative content analysis. Methods are reported using COREQ guidelines. Results: We found that the meaning of living with open surgical wounds is shaped by five subthemes: "enduring healing", "life disruption", "adapting to a new reality", "striving for healing" and "returning to normal life;" all under an overarching theme of "negotiating a new normality". Conclusion: Participants' well-being and everyday living are greatly impacted by open surgical wounds. Findings from this study emphasize that open surgical wounds are a long-term condition with a typical "chronicity" trajectory; this brings a new perspective to previous findings of studies on living with complex wounds. This study has also highlighted areas for further research, related to improving individuals' experience of living with open surgical wounds.